Synthesis of the Marine Pyrroloiminoquinone Alkaloids, Discorhabdins - Wada, Yasufumi (Molecular Diversity Preservation International, 2010)
Many natural products with biologically interesting structures have been isolated from marine animals and plants such as sponges, corals, worms, etc. Some of them are discorhabdin alkaloids. The discorhabdin alkaloids (discorhabdin A-X), isolated from marine sponges, have a unique structure with azacarbocyclic spirocyclohexanone and pyrroloiminoquinone units. Due to their prominent potent antitumor activity, discorhabdins have attracted considerable attention. Many studies have been reported toward the synthesis of discorhabdins. We have accomplished the first total synthesis of discorhabdin A (1), having the strongest activity in vitro among discorhabdins in 2003. In 2009, we have also accomplished the first total synthesis of prianosin B (2), having the 16,17-dehydropyrroloiminoquinone moiety, by a novel dehydrogenation reaction with a catalytic amount of NaN(3). These synthetic studies, as well as syntheses of the discorhabdins by various chemists to-date, are reviewed here.